ARTIFICIAL INTELLIGENCE CAPABILITIES IN THE COACHING PROCESS (PERSONALIZATION, ADAPTIVE LEARNING) (International journal of artificial intelligence, 2025)
This article analyzes the possibilities of using artificial intelligence (AI) in the mentoring process for personalization and adaptive learning. In the modern educational environment, an individual approach and comprehensive development of learners are of great importance. AI technologies assist mentors in tailoring the learning process to the abilities and needs of students. The study examines methods for delivering AI-based personalized learning materials and adapting the teaching process in real time. The results indicate that artificial intelligence is a crucial tool for enhancing the effectiveness of mentoring, as well as increasing student engagement and motivation. At the same time, pedagogical and ethical aspects of technology use must be taken into consideration.